Beyond Words: A Systemic Functional Linguistic Approach to Silence, Omission, And Trauma in Literary Narrative - Karisma Tarigan (Journal of linguistics, culture and communication, 2026)
This study aims to investigate how silence and omission in literary trauma narratives are linguistically encoded through transitivity structures within the Systemic Functional Linguistics (SFL) framework. While prior research has examined trauma disclosure and silence as social or psychological phenomena, the systematic grammatical encoding of omission has received less attention. Using Hanya Yanagihara's a Little Life as a case study, a qualitative textual analysis was performed following a three-step process: identifying passages relevant to trauma, segmenting clauses and coding transitivity across six process categories, and aggregating and interpreting patterns. A total of 149 clauses were examined. The analysis revealed 64 instances of omission, demonstrating that omission is a systematic component of the data. Omission patterns include Senser omission in 23% of Mental processes, Actor omission in 33% of Material processes, Verbiage omission in 50% of Verbal processes, Carrier omission in 14% of Relational processes, and Process omission in 50% of Existential processes. Existential and verbal processes comprise only 1% and 8% of all clauses, respectively. These results demonstrate that silence in trauma narratives represents a structured grammatical decision rather than a mere absence of language, providing a replicable framework for analyzing omission and advancing both linguistic analysis and trauma studies